2018
DOI: 10.1371/journal.pone.0204121
|View full text |Cite
|
Sign up to set email alerts
|

Biogas residue parameterization for soil organic matter modeling

Abstract: A variety of biogas residues (BGRs) have been used as organic fertilizer in agriculture. The use of these residues affects the storage of soil organic matter (SOM). In most cases, SOM changes can only be determined in long-term observations. Therefore, predictive modeling can be an efficient alternative, provided that the parameters required by the model are known for the considered BGRs. This study was conducted as a first approach to estimating the organic matter (OM) turnover parameters of BGRs for process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
0
12
1
1
Order By: Relevance
“…The decomposition rate coefficient k describes the rate of organic matter decay and the synthesis coefficient η describes SOM creation from BGR. These values were calculated from the pH and C/N ratio according to Prays et al (2017).…”
Section: Biogas Plant and Bgrmentioning
confidence: 99%
See 2 more Smart Citations
“…The decomposition rate coefficient k describes the rate of organic matter decay and the synthesis coefficient η describes SOM creation from BGR. These values were calculated from the pH and C/N ratio according to Prays et al (2017).…”
Section: Biogas Plant and Bgrmentioning
confidence: 99%
“…In our model, the higher residence time is a consequence of the improved transfer of carbon from fresh organic matter to the SOM pools. The SOM synthesis coefficient η of BGR is higher than that of cattle slurry or manure, and thus its contribution to SOM is higher (Prays et al, 2017). Numerous studies have compared BGRs with other organic amendments (Abubaker et al, 2013a;Abubaker et al, 2013b;Möller and Stinner, 2009;Stumpe et al, 2012) and concluded that there is no long-term negative effect on the SOC if manures are anaerobically digested.…”
Section: Corg Development After the Implementation Of The Biogas Plantmentioning
confidence: 99%
See 1 more Smart Citation
“…The decomposition rate coefficient k describes the rate of organic matter decay and the synthesis coefficient η describes SOM creation from BGR. These values were calculated from the pH and C/N ratio according to Prays, Sänger, Dominik, and Franko (2017).…”
Section: Biogas Plant and Bgrmentioning
confidence: 99%
“…In our model, the higher residence time is a consequence of the improved transfer of carbon from fresh organic matter to the SOM pools. The SOM synthesis coefficient η of BGR is higher than that of cattle slurry or manure, and thus its contribution to SOM is higher (Prays et al, 2017). Numerous studies have compared BGRs with other organic amendments (Abubaker, Cederlund, Arthurson, & Pell, 2013;Abubaker, Odlare, & Pell, 2013;Möller & Stinner, 2009;Stumpe et al, 2012) and concluded that there is no long-term negative effect on the SOC if manures are an aerobically digested.…”
Section: After Biogas Plant Implementationmentioning
confidence: 99%